2015
DOI: 10.1002/pro.2852
|View full text |Cite
|
Sign up to set email alerts
|

Artificial domain duplication replicates evolutionary history of ketol‐acid reductoisomerases

Abstract: The duplication of protein structural domains has been proposed as a common mechanism for the generation of new protein folds. A particularly interesting case is the class II ketolacid reductoisomerase (KARI), which putatively arose from an ancestral class I KARI by duplication of the C-terminal domain and corresponding loss of obligate dimerization. As a result, the class II enzymes acquired a deeply embedded figure-of-eight knot. To test this evolutionary hypothesis we constructed a novel class II KARI by du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The E. coli IlvC also showed NADPH reduction. The E. coli IlvC protein has a higher K m value for acetolactate, 250±30 µM, as compared to IlvC of Mtb (K m for acetolactate=110±4 µM protein) [10,25]. The NADPH reduction confirmed that both Mtb-Ra and E. coli IlvCs were functional ketol-acid reductoisomerases and Mtb-Ra enzyme was able to complement the functionalities of E. coli enzyme.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The E. coli IlvC also showed NADPH reduction. The E. coli IlvC protein has a higher K m value for acetolactate, 250±30 µM, as compared to IlvC of Mtb (K m for acetolactate=110±4 µM protein) [10,25]. The NADPH reduction confirmed that both Mtb-Ra and E. coli IlvCs were functional ketol-acid reductoisomerases and Mtb-Ra enzyme was able to complement the functionalities of E. coli enzyme.…”
Section: Discussionmentioning
confidence: 82%
“…The E. coli IlvC protein has a higher K m value for acetolactate, 250±30 µM, as compared to IlvC of Mtb ( K m for acetolactate=110±4 µM protein) [10, 25]. The NADPH reduction confirmed that both Mtb -Ra and E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that ancient domains arose by fusion of short peptide ancestors and that they are further diversified by fusion with other domains. Recently, researchers tested how duplicated domains formed through biological experiment (Cahn et al, 2016 ). They tested the possibility whether the class II ketol-acid reductoisomerase (KARI) have been produced from an ancestral class I KARI by duplication of the C-terminal domain and corresponding loss of obligate dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that recombination events can add or remove whole domains constituting long-scale mechanisms for domain architectural change 67 . In this context, tandem domain duplication provides a particular mechanism for modifying the oligomeric state of an enzyme without altering its function [68][69][70][71] . This occurred in the evolution of dimeric 6PGDHs, with the additional consideration that the duplication lead to the loss of two active sites in the oligomeric assembly.…”
Section: Discussionmentioning
confidence: 99%